Polyphenolics from albizia harveyi exhibit antioxidant activities and counteract axidative damage and ultra-structural changes of cryopreserved bull semen - Sobeh, Mansour; Hassan, Soha A.; El Raey, Mohamed A.; Khalil, Wael A.; Hassan, Mahmoud A. E.; Wink, Michael (Molecules, 2017)
Albizia harveyi is a tropical deciduous tree, found across South and Eastern Africa and widely used in traditional medicine. The leaf extract ameliorated the damaging effects of the frozen-thawing process in cryopreserved bull semen. In a dose-dependent pattern, sperm motility, viability, and membrane integrity were improved compared to the untreated control. Furthermore, the extract increased the percentage of viable sperm cells and reduced the percentages of early apoptotic and apoptotic sperm cells as well as the damage in sperm ultra-structure. These activities are in agreement with the robust antioxidant properties in vitro and in the seminal fluid as observed in the total antioxidant capacity and the lipid peroxidation parameter malondialdehyde. LC-MS yielded 35 compounds. The extract was dominated by quercetin-O-galloyl-hexoside and quercetin-O-pentoside, along with other flavonoid glycosides. The polyphenols are probably responsible for the observed activities. In conclusion, the current findings show that A. harveyi leaves are rich in bioactive polyphenols with functional properties, validating its traditional use.
Gesehen am 17.04.2020